Andreev reflection spectroscopy of the new Fe-based superconductor EuAsFeO0.85F0.15: evidence for the strong order parameter anisotropy - Dmitriev, V.M.; Khlybov, E.P.; Kondrashov, D.S.; Terekhov, A.V.; Rybaltchenko, L.F.; Khristenko, E.V.; Ishchenko, L.A.; Kostyleva, I.E.; Zaleski, A.J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Andreev reflection spectra have been measured in a new superconductor EuAsFeO0.85F0.15 having an unexpectedly low superconducting transition temperature Tc ≈ 11.3 K among related FeAs compounds on a base Sm and Gd surrounding Eu in the series of lanthanides. The nearly fivefold lower Tc, as against the expected value, is attributed to the divalent properties of Eu ions when in the compound investigated along with the weaklymagnetic Eu3+ ions may be present and the strongly magnetic Eu2+ ones that is a strong destructive factor for superconductivity. Most of the spectra measured showed features that corresponds to two energy gaps whose values varied from contact to contact within 2Δs/kTc = 2.2–4.7 and 2Δ1/kTc = 5.1–11.7 for small and large gap, respectively. The corresponding variations for single-gap spectra are 2Δ/kTc = 2.6–6.4. The relatively large size of crystallites (no less than ~25 μm) and the large number of contacts measured (several tens) suggest with a high degree of probability that the spectra obtained account quite fully for the gap distribution practically in all crystallographic directions. The data obtained and the absence of zero gaps in the measured spectra evidence in favor of the anisotropic s- or s±-symmetry of the order parameter in EuAsFeO0.85F0.15 that was revealed in other similar compounds with higher Tc. Thus, the character of the gap function Δ(k) in this compound is inconsistent with the d-wave superconductivity observed in some low-Tc pnictides.